SERVICE PERFORMANCE EVALUATION IN LARGE RAILWAY STATION IN INDONESIA - A. Caroline Sutandi; Floid Olzon Paladan (Jurnal Transportasi, 2016)
Abstract People need transportation for social and economic daily activities. Since road network usually experience traffic congestion, railroad is one of good alternatives. People will choose train as a public transportation if there is a good service performance. In accordance with domestic and international social and economic activities in Indonesia, national and international service standard is important. The aim of this study is to evaluate the service performance of large railway station in a large city in developing country. Bandung large railway station is carried out as a case study. Indonesian transportation minister regulation No. 48 year 2015 regarding people transport by train and Department for Transport Scotland, 2015 regarding design standards for accessible railway stations used as the standards. Results indicated that waiting room, boarding room, and prayer room fulfill the standards while restroom, lighting, and air-conditioner are unfulfilled. Furthermore, improvement, routine inspection, and maintenance have to be implemented consistently. Keywords: service performance, large railway station, large city, developing country  Abstrak Manusia memerlukan transportasi dalam kegiatan sosial dan ekonomi sehari-hari. Jaringan jalan umumnya selalu mengalami kemacetan lalulintas, karenanya jalan rel adalah alternatif yang baik. Orang akan memilih kereta api sebagai moda transportasi publik jika terdapat pelayanan yang baik. Berkenaan dengan kegiatan sosial dan ekonomi yang bertaraf nasional dan internasional di Indonesia, maka pemenuhan terhadap standar pelayanan nasional dan internasional menjadi penting. Tujuan studi adalah mengevaluasi kinerja pelayanan stasiun besar kereta api di kota besar di negara berkembang. Stasiun besar kereta api Bandung digunakan sebagai studi kasus. Peraturan Menteri Perhubungan Republik Indonesia No. 48 Tahun 2015 tentang Standar Pelayanan Minimum Angkutan Orang dengan Kereta Api dan Standar Department for Transport Scotland, 2015 tentang Standar Desain untuk Stasiun Kereta Api yang mudah diakses digunakan sebagai pedoman. Ruang tunggu, ruang boarding, dan mushola memenuhi kedua standar. Toilet, penerangan, dan sistem pendingin ruangan tidak memenuhi kedua standar. Selanjutnya perbaikan, inspeksi rutin, dan pemeliharaan harus konsisten dilakukan. Kata-kata kunci: kinerja pelayanan, stasiun besar kereta api, kota besar, negara berkembang